PENGARUH OPINI AUDIT, UKURAN KAP DAN PERGANTIAN MANAJEMEN TERHADAP AUDITOR SWITCHING DENGAN FINANCIAL DISTRESS SEBAGAI VARIABEL MODERASI - Frisylia Assyifa Hamzah; Harry Budiantoro; Kanaya Lapae; Hestin Agus Tantri Ningsih (Jurnal Education and Development, 2023)
The purpose of this study is to see how audit opinion, KAP size, and management turnover affect auditor switching, with financial distress as a moderating variable. Between 2015-2020, the population of various industrial companies listed on the Indonesia Stock Exchange (IDX) was used for this study. Purposive sampling was used in this study, and the samples obtained were 11 companies. Secondary data used in this study from annual financial statements obtained from the official website of the Indonesia Stock Exchange (IDX). With SPSS version 25.0 application, logistic regression analysis method is used. The findings show that audit opinion, KAP size, and management turnover have no effect on auditor switching, and financial distress cannot moderate the effect of audit opinion, KAP size, and management turnover on auditor switching.